ANALISIS KEPUTUSAN PEMBELIAN MELALUI KUALITAS PELAYANAN, KUALITAS PRODUK, DAN HARGA PADA SIARAN TV KABEL PESONA DI PULAU KANGEAN KEC. ARJASA - Ahmad Fawaid; Ida Aryati; Raisa Aribatul Hamidah (JURNAL ILMIAH EDUNOMIKA, 2023)
The purpose of this study was to determine the effect of service quality, product quality, and price on purchasing decisions on Pesona Cable TV broadcasts on Kangean Island, Kec. Arjasa. Researchers used a descriptive quantitative approach. The research was conducted on Kangean Island, Kec. Arjasa. This research was conducted for 3 months, namely during October-December 2022. The population used in this study were subscribers who used Pesona cable TV broadcasts on Kangean Island, Kec. Arjasa, which has 1,233 customers. The researcher chose 123 respondents who use Pesona cable TV as a sample. The technique of determining the sample from this study uses the probability sampling method. The results of this study indicate that based on the t test, the results of service quality, product quality, and price have a positive and significant effect on purchasing decisions on Pesona Cable TV broadcasts on Kangean Island, Kec. Arjasa. Based on the F test, it shows that service quality, product quality, and price have a simultaneous and significant effect on purchasing decisions on Pesona Cable TV Broadcasts on Kangean Island, Kec. Arjasa. Keywords: Product Quality, Lifestyle, Quality of Service Purchasing Decisions.